Neural signatures underlying deliberation in human foraging decisions - Abram, Samantha V. (Cogn Affect Behav Neurosci, 2019)
Humans have a remarkable capacity to mentally project themselves far ahead in time. This ability, which entails the mental simulation of events, is thought to be fundamental to deliberative decision-making as it allows us to search through and evaluate possible choices. Many decisions that humans make are foraging decisions, where one must decide whether an available offer is worth taking, when compared to unknown future possibilities (i.e., the background). Using a translational decision-making paradigm designed to reveal decision-preferences in rats, we found that humans engaged in deliberation when making foraging decisions. A key feature of this task is that preferences (and thus, value) are revealed as a function of serial choices. Like rats, humans also took longer to respond when faced with difficult decisions near their preference boundary, which was associated with prefrontal and hippocampal activation, exemplifying cross-species parallels in deliberation. Furthermore, we found that voxels within visual cortices encoded neural representations of available possibilities, specifically following regret-inducing experiences, in which the subject previously rejected a good offer only to encounter a low-valued offer on the subsequent trial.